2020
DOI: 10.4081/ejh.2020.3169
|View full text |Cite
|
Sign up to set email alerts
|

Swertiamarin suppresses proliferation, migration, and invasion of hepatocellular carcinoma cells <em>via</em> negative regulation of FRAT1

Abstract: Studies have shown that swertiamarin (STM) has multiple biological activities, but its anti-tumour effects and molecular mechanisms are still unclear. The present research aimed to validate the STM’s impacts on the proliferation, migration, and invasion of hepatocellular carcinoma (HCC) cells, and to study its potential mechanism. Two HCC cell lines were treated with STM. Tumour growth was observed by the mouse tumour xenografts model. HCC cell lines stably expressing T-cell lymphomas 1 (FRAT1) were generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…To the best of our knowledge, the role of FraT1 and VeGFa in glioma, prognosis and diagnosis, was investigated for the first time in the present study, based on using the TcGa database and physiological and biochemical methods. The results demonstrated that the expression of FraT1 and VeGFa in pan-cancer was similar to that seen in certain previous studies (62,63). Furthermore, FraT1 and VeGFa mrna expression levels were significantly increased in GBMLGG compared with normal tissues.…”
Section: Discussionsupporting
confidence: 89%
“…To the best of our knowledge, the role of FraT1 and VeGFa in glioma, prognosis and diagnosis, was investigated for the first time in the present study, based on using the TcGa database and physiological and biochemical methods. The results demonstrated that the expression of FraT1 and VeGFa in pan-cancer was similar to that seen in certain previous studies (62,63). Furthermore, FraT1 and VeGFa mrna expression levels were significantly increased in GBMLGG compared with normal tissues.…”
Section: Discussionsupporting
confidence: 89%
“…Waltonitone isolated from G. waltonii induces tumor cell cycle arrest through regulating Akt and ERK1/2 pathways, thereby inhibiting tumor cell growth [118]. Swertiamarin had certain inhibitory and pro-apoptotic effects on hepatocellular carcinoma cells in vitro [119]. Swertiamarin and mangiferin from S. davidii are the main active substances that inhibit growth and induce apoptosis in HepG2 human liver cancer cells [120].…”
Section: Anticancermentioning
confidence: 99%
“…Secoiridiods are characteristic substances of MR, while their contents are very low. Studies have indicated that secoiridiod glycosides possess wide biological activities such as anti-inflammatory and immunoregulatory ( Saravanan et al, 2014a ; Saravanan et al, 2014b ; Wang et al, 2019a ), analgesic ( Liu et al, 2016 ; Garrido-Suárez et al, 2020 ), anti-tumor ( Tang et al, 2019 ; Xiao et al, 2020 ) hepatoprotective ( Shao et al, 2017 ; Wu et al, 2017 ), hypoglycemic ( Vaidya et al, 2013a ; Dhanavathy, 2015 ; Vaidya et al, 2012 ; Vaidya et al, 2009 ), neuroprotective ( Wang et al, 2019b ; Wu et al, 2019 ) effects.…”
Section: Phytochemistrymentioning
confidence: 99%
“…Recently, it has revealed that SWM suppresses proliferation, migration, and invasion of HCCs ( Xiao et al, 2020 ). The cell viability was assayed by the CCK8 method.…”
Section: Pharmacological Effectsmentioning
confidence: 99%
See 1 more Smart Citation